Analysis of public policies related to improving the lives of older adults during COVID pandemics in Carchi province - López Cadena, Yessenia Katherine; Ramos Guerrero, Fernanda Catalina (SATHIRI, 2023)
Public policies are the essential tools to achieve good management and distribution of resources, seeking to meet the needs of citizens, especially the elderly, since they are a vulnerable group that needs more attention due to the needs and requirements they present, that is, so public policies are the means by which a dignified life and old age is guaranteed. The present investigation diagnosed the public policy in relation to the improvement of the lives of older adults in the Province of Carchi in times of pandemic, the sample consisted of 383 older adults belonging to the social registry and independent associations in the Province of Carchi. The results showed significant differences between public policies and their impact on the improvement of the living conditions of the elderly population, in this sense, despite the existence of public policies and laws for the benefit of this vulnerable group, the management was framed in the continuity of programs and projects implemented previously and it was evidenced that no projects were incorporated for the pandemic as such, causing a attention deficit in the elderly, limiting their actions and accompanying activities towards this vulnerable group, increasing their physical and emotional health in the global crisis, in addition, a homogeneous service is not provided throughout the province of Carchi, since there is no All parishes have promoters who work with the elderly who need it most. Finally, it is proposed to identify the public policies aimed at this population such as the elderly in the province of Carchi, to examine the public management carried out by the MIES as the leading institution in the care of priority attention groups; as well as to build a proposal for a public policy of protection for the elderly in the province. It is concluded that the competent public institutions should put more emphasis on an adequate management, in order to meet the needs related to health, quality of life and citizen participation for the benefit of a social integration that allows the elderly to be a visible individual in society.
Keywords: Older adults; quality of life; pandemic; public policies; citizen participation